2021
DOI: 10.1038/s41467-021-22981-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution and the decline of purifying selection with age

Abstract: Life history theory predicts that the intensity of selection declines with age, and this trend should impact how genes expressed at different ages evolve. Here we find consistent relationships between a gene’s age of expression and patterns of molecular evolution in two mammals (the human Homo sapiens and the mouse Mus musculus) and two insects (the malaria mosquito Anopheles gambiae and the fruit fly Drosophila melanogaster). When expressed later in life, genes fix nonsynonymous mutations more frequently, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…Our model also allows us to quantify the tissue-specific evolutionary context of age-associated gene expression changes. We corroborate the inverse relationship between age-at-expression and constraint, as predicted by Medawar’s hypothesis and recently documented by others (8, 9, 19) across the vast majority of tissues. However, we also surprisingly identify five tissues which exhibit the opposite pattern and show that age-associated signatures of increased proliferation and cancer are enriched in these tissues.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our model also allows us to quantify the tissue-specific evolutionary context of age-associated gene expression changes. We corroborate the inverse relationship between age-at-expression and constraint, as predicted by Medawar’s hypothesis and recently documented by others (8, 9, 19) across the vast majority of tissues. However, we also surprisingly identify five tissues which exhibit the opposite pattern and show that age-associated signatures of increased proliferation and cancer are enriched in these tissues.…”
Section: Discussionsupporting
confidence: 92%
“…5A). Several recent studies have demonstrated the generality of this trend across species (8, 9, 19) however the tissue-specificity of this theoretical prediction has not been explored. We sought to test the generality of this trend across different tissues by comparing β age with the level of constraint on genes, quantified as the probability loss of function intolerance (pLI) score from gno-mAD (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression in the testis is often an outlier compared to other tissues (Witt et al, 2021b), so the results of these two studies are not necessarily in conflict. Nevertheless, the consistent pattern between this study and that of Cheng and Kirkpatrick (Cheng and Kirkpatrick, 2021) is that that genes enriched in late spermatids have a higher dN/dS than those enriched in early germ cells. In this way, at both whole-organism development and germline development level, late-stage biased genes tend to evolve more rapidly.…”
Section: Discussionsupporting
confidence: 87%
“…Second, since we used the scaled expression, old-enriched genes may reflect a specific set of genes that are essential for aging animals, which may be more likely to be house-keeping genes. Our results are interesting in the light of recent work which found that genes expressed later in life tend to fix nonsynonymous mutations more frequently (Cheng and Kirkpatrick, 2021). One should note that their methodology is different: their age-biased genes were identified from whole-body data, whereas ours were calculated just from male germ cells.…”
Section: Discussionmentioning
confidence: 79%